Does the Law of One Price Hold in International Financial Markets? Evidence from Tick Data - Q. Farooq Akram; Dagfinn Rime; Lucio Sarno (Norges Bank, 2008)
This paper investigates the validity of the law of one price (LOP) in international financial markets by examining the frequency, size and duration of inter-market price differentials for borrowing and lending services (`one-way arbitrage'). Using a unique data set for three major capital and foreign exchange markets that covers a period of more than seven months at tick frequency, we find that the LOP holds on average, but numerous economically significant violations of the LOP arise. The duration of these violations is high enough to make it worthwhile searching for one-way arbitrage opportunities in order to minimize borrowing costs and/or maximize earnings on given funds. We also document that such opportunities decline with the pace of the market and increase with market volatility.
hdl:11250/2497766
Keywords: F31; F41; G14; G15; 330; law of one price; one-way arbitrage; foreign exchange microstructure